The Effectiveness of Filopaludina javanica and Sulcospira testudinaria in Reducing Organic Matter in Catfish (Clarias sp.) Aquaculture Wastewater - Shofiyatul Lailiyah; Diana Arfiati; Asus Maizar Suryanto Hertika; Neni Diah Kusumaning Arum; Catur Budi Noviya (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
HighlightCatfish aquaculture wastewater contains organic matter that exceeds the quality standard of 68.75 mg / L and 72.48 mg / L.Tutut Jawa snail (F. javanica) can reduce organic matter in waste by up to 92%.Susuh Kura snail (S. testudinaria) can reduce organic matter in waste by up to 87%.Catfish aquaculture wastewater treatment with snails only takes 8 hours. Abstract The residual or wastewater from the cultivation process that is discharged directly into common waters can reduce the quality of the waters because it contains a lot of organic material from organism feces and feed residue, so it needs management first. The purpose of this study was to determine the ability of Javanese snails and freshwater gastropods to reduce total organic matter in catfish culture waste. The research method used was the experiment with 2 factor Factorial completely randomized design, namely the measurement time (4, 8, 12, and 16 hours) and the abundance of the Tutut Java snail and freshwater gastropods (100%, 75%, 50%, 25%, and control) with 5 repetitions. Tutut Java snails were taken from the pond at UPR Sumbermina Dau and brought to the laboratory. The results obtained in the treatment with the addition of  Tutut Java snail, the total organic matter content decreased at 75% snail density by 90% (from 68.75 mg / L to 5.31 mg / L) at the 12th hour. The treatment with the addition of Freshwater Gastropods at a density of 25%, the total organic matter content decreased by 87% (from 72.48 to 9.35 mg / L) at the 8th hour. Water quality during the study was in a condition that could tolerate the Tutut Java snails and freshwater gastropods. The conclusion is that the addition of Tutut Java snail and / or freshwater gastropods can reduce the total organic matter content to the water quality standard.